Kebijakan Standar Nasional Pendidikan - Miftahul Ulum (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Abstract: National Education Standards are minimum criteria regarding the education system in the entire jurisdiction of the Unitary Republic of Indonesia. The policy regarding National Education Standards is contained in Government regulation No. 19 of 2005 This regulation is a translation of Law No. 20 of 2003 concerning the National Education System. And along with the enactment of the 2013 curriculum, the policy changed to Government Regulation No. 32 of 2013 concerning Amendments to Government Regulation No. 19 of 2005 concerning National Education Standards. National Education Standards contain 8 minimum criteria which include: graduate competency standards, content standards, process standards, teacher and education staff standards, facilities and infrastructure standards, management standards, financing standards, education assessment standards.